Assessment of Work Posture on Woven Bamboo Craftsmen - Isyeu Sriagustini; Teni Supriyani (Universitas Airlangga, 2022)
Introduction: The industry in Indonesia is still experiencing a rapid development. Woven craft one of the thriving informal sector businesses in Tasikmalaya Regency. Each stage of work on making bamboo woven crafts is done in a way that is not ergonomic, especially in the working position, namely how to sit or squat on the floor with the head and back bent. This condition can cause musculoskeletal disorders. The results of risk analysis showed that the job position that belongs to a high-risk category must be controlled immediately. The aim of this study is to assess the working posture of woven bamboo craftsmen. Methods: This research is descriptive research. The object under study was the 20 stages of production of woven bamboo handicraft products. The variables studied were work positions, including individual characteristics and musculoskeletal complaints. Data were collected through passive participant observation using observation sheets. Work position data analysis was carried out using the RULA assessment table. Results: Work postures at thirteen stages of work were at action level 2, three stages of work were at action level 3, and two stages of work were at action level 4. In general, the craftsmen complained of aches in the waist (28%), hand pain (19%), leg pain (16%), and back pain (12%). Conclusion: Priority control should carried out at the coloring and drying stages because they have an action level 4 that must implement the changes now.